1987
DOI: 10.2118/14888-pa
|View full text |Cite
|
Sign up to set email alerts
|

Geologic Problems Related to Characterization of Clastic Reservoirs for EOR

Abstract: Geologic problems encountered in four U.S. DOE-sponsored EOR projects in clastic reservoirs were analyzed. The reservoir heterogeneities were grouped into four categories: depositional, diagenetic, structural, and formation-fluid composition/distribution. Each category had a variable effect on the performance of the EOR projects.Requirements for developing one static geologic model for each category of heterogeneity are proposed. The interrelationship of geologic factors and the effect of heterogeneities resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…3), did not provide the anticipated recovery. Subsequent data analyses [14][15][16] indicated that reservoir geology and the poor quality of sulfonate used in the polymer flood were probably responsible for the less-than-optimum recovery. As discussed previously, the relatively poorer permeability and porosity of the sediments deposited under lower-energy conditions in this region resulted in more clay content in the sandstone, although faulting or the presence of a permeability barrier is also suspected in the eastern part of the pilot and may have contributed to the poor sweep and displacement efficiencies of the chemical flood.…”
Section: Areal Productivity Distribution Of Barrier Island Sandstonementioning
confidence: 99%
See 1 more Smart Citation
“…3), did not provide the anticipated recovery. Subsequent data analyses [14][15][16] indicated that reservoir geology and the poor quality of sulfonate used in the polymer flood were probably responsible for the less-than-optimum recovery. As discussed previously, the relatively poorer permeability and porosity of the sediments deposited under lower-energy conditions in this region resulted in more clay content in the sandstone, although faulting or the presence of a permeability barrier is also suspected in the eastern part of the pilot and may have contributed to the poor sweep and displacement efficiencies of the chemical flood.…”
Section: Areal Productivity Distribution Of Barrier Island Sandstonementioning
confidence: 99%
“…The second micellar-polymer pilot was located in the central part (the TIP area) 14,16 of Unit A (location in Fig. 3) where the highly productive facies is thick and the sandstones have good porosity and permeability, except in a small area in the southwest of the TIP area.…”
Section: Areal Productivity Distribution Of Barrier Island Sandstonementioning
confidence: 99%
“…Problems related to reservoir heterogeneity encountered in four EOR pilot projects in clastic reservoirs sponsored by the Department of Energy (DOE) were analyzed in detail by Szpakiewicz et al (1987). Two of these reservoirs, the Big Muddy field producing from the Upper Cretaceous Frontier formation in Wyoming and the Bell Creek field producing from the Lower Cretaceous Muddy formation have been classified as barrier island deposits (i.e., Class 4).…”
Section: 1 2 Natural Sources Of Heterogeneitymentioning
confidence: 99%
“…The Bell Creek field consists of six separate barrier island reservoir compartments in which the trapping mechanism is the updip pinch-out of barrier core facies into lagoonal shales. The predominant heterogeneities affecting production in this micellar-polymer project were (1) facies architecture and the presence of incised valleys with lithologically variable fill (Szpakiewicz et al, 1987;Honarpour et al, 1988;Sharma et al, 1990;Burt et al, 1975); (2) distribution, type, and amount of authigenic clay minerals; and (3) presence of previously unrecognized fractures and faults between wells and groups of wells. Production data and pressure-pulse tests confirmed many of these naturally occurring heterogeneities, but interpretation of tracer survey results was not clear because of chemical interaction between the preflush and micellar-polymer solution (Szpakiewicz et al, 1987).…”
Section: 1 2 Natural Sources Of Heterogeneitymentioning
confidence: 99%
“…In tight formations, which can include sandstones, shales, limestones, and coal, often the only practical means to extract hydrocarbons is by exploiting the increased drainage surface provided by natural fracture zones (Szpakiewicz et al, 1986;Lorenz et al, 1986). The practical difficulties that must be overcome before effectively using these fractures include: locating the position and orientation of fracture zones, determining the intensity of fracturing, and characterizing the spatial relationships of these fractures relative to reservoir heterogeneities which might enhance or inhibit the eventual gas flow.…”
Section: Introductionmentioning
confidence: 99%